INDUSTRIAL POLICY IN ASIAN NEWLY INDUSTRIALIZED COUNTRIES: CONTROVERSIES, REVIEW AND LESSONS - Dejana Gajinov (Acta Economica)
The paper’s aim is to use the successful example of the newly industrialized Asian countries, as well as the countries of the East Asian region in general, to prove the need to implement industrial policy in many countries, both those lagging behind in industrial development and those that have reached the technological frontier. The paper describes the evolution of industrial policy in these countries and what distinguishes them from other developing countries that were unsuccessful in its implementation: the developmental state, which recognized timely the turning point from the strategy of import substitution to the strategy of export promotion, implemented both strategies simultaneously, picked winners, provided support to infant industries through selective interventions, but also disciplined the recipients of its support, tracked its own comparative advantages and anticipated their changes, with a strong synergy between the state and private sectors, and looking at Japan as a model of industrial development, i.e. the lead goose. Industrial policy is one of the most controversial issues in economics. There has been a long debate between two schools of thought - orthodoxy and heterodoxy - as to whether there is a need for industrial policy in general, as well as the role of the state in the process of its creation and implementation, as opposed to the free market model of development in which there is no place for industrial policy, and if it appears it can be only of a general nature, and by no means in the form of selective interventions. Over the last 10 to 15 years, there has been a revision both at the academic level and in the real world that has made industrial policy more acceptable, and thus the debate about it has become less ideologically colored and more pragmatic and nuanced. At the theoretical level, the market fundamentalist view of little theoretical justification for industrial policy has lost its dominance. Despite maintaining neoliberal orthodoxy as the advice of international financial institutions in the process of creating economic policy in developing countries, industrial policy remained important for the promotion of industrial development, especially the infant industries. It is accepted that there are many types of market failures that must be addressed through industrial policy. It is increasingly recognized that industrial policy is not just a highly idiosyncratic practice associated only with the miracle economies of East Asia, but what most of today’s developed countries used when they were in the position of the catching-up countries. As a conclusion, the paper discusses the possibility of transferring the East Asian model to other countries, and sheds light on the determinants of industrial policy success and failure. The key conclusion is that there is room for successful industrial policy even in countries that have reached the technological frontier and want to push it further, as well as in countries lagging behind in industrial development, although the global context in which industrial policy is situated has changed over time. A special commentary is referred to the economic and industrial development of the former countries of Yugoslavia.